Mastering Selenium WebDriver 3. 0 : Boost the Performance and Reliability of Your Automated Checks by Mastering Selenium WebDriver, 2nd Edition. - Patrick Leigh Collin, Mark (Packt Publishing Ltd, 2018)
Selenium WebDriver is an automation tool used by software developers to test the web applications. In this book you will gain a deep understanding of Selenium as a test tool and learn series of strategies that will help you create reliable and extensible test frameworks. Also focus on Java WebDriver API and learn to run tests on multiple browsers.